The competitiveness of brazilian beef in the light of Porter's five forces: a case study in a slaughterhouse in the northwest region of Rio Grande do Sul (Research, Society and Development, 2021)
The beef market presents data that place Brazil in a prominent position in the global scenario, both as a producer and as a consumer. Thus, the present study has, as a central objective, to investigate the competitiveness of Brazilian beef, in the light of the Porter's five forces model. The research methodology relies on a single case study, carried out in a slaughterhouse located in the Northwest Region of the state of Rio Grande do Sul. With a qualitative approach, the research was operationalized through a semi-structured interview with a manager and the respective content analysis, to work the links in the beef production chain, to variations in consumer demand and possible cultural and economic changes. The research findings point to a positive fluctuation in the demand for beef, which shows the strength of this market, both in the national and international scenario. Still, some threats to this demand are present, such as the growth of vegetarian culture.